Ethnopsychiatry Nursing: A Transformative Model for Patient-Centered Care in Diverse Societies - Indi Dwi Shofi Yanti; Fatma Lutfiyatus Sayyida; Anggun Novia Indah Fitri (Tarqabin Nusantara Group, 2025)
In an era marked by increasing cultural diversity and global migration, mental health care must adapt to address the unique needs of heterogeneous populations. Ethnopsychiatry nursing emerges as a pivotal interdisciplinary approach that integrates psychiatric knowledge with cultural anthropology to enhance the understanding of how culture influences mental illness experiences, expressions, and treatment responses. This systematic literature review synthesizes current evidence on ethnopsychiatry nursing using a PRISMA-guided methodology, identifying seven core domains: foundational concepts, cultural competence frameworks, clinical strategies, care delivery models, social context integration, specialized interventions for migrant populations, and implementation challenges. Drawing on theoretical foundations such as Kleinman’s Explanatory Model of Illness, Campinha-Bacote’s Cultural Competence model, and Metzl & Hansen’s Structural Competence framework, this review highlights practices that improve diagnostic accuracy, therapeutic engagement, and patient trust. Findings underscore the necessity of culturally sensitive diagnosis, structural advocacy, and patient-centered approaches to counter systemic inequities including racism, immigration trauma, and socioeconomic disparities. Despite growing recognition, implementation remains inconsistent due to ethnocentric biases, lack of standardized protocols, and ethical complexities. The study proposes actionable strategies for advancing education, institutional support, and policy reform to ensure equitable, culturally responsive mental health care. By prioritizing the lived experiences of marginalized communities, ethnopsychiatry nursing contributes to building inclusive, ethical, and effective mental health systems.